2017
DOI: 10.5664/jcsm.6846
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sleep for Hospitalized Antepartum Patients: A Non-Randomized Controlled Pilot Study

Abstract: Study Objectives: To evaluate feasibility and efficacy of a hospital-based protocol for improving sleep in high-risk antepartum patients. Methods: Sleep measures were compared during 1 week of hospitalization before and after implementing a Sleep Improvement Protocol for Antepartum Patients (SIP-AP). A non-randomized convenience sample of usual care controls was compared to a subsequent intervention sample after the protocol was implemented. Women were eligible if they spoke English, were medically stable, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Of the included studies, six were RCT [43][44][45][46][47][48], testing the efficacy of the following different interventions: use of lavender cream, pharmacotherapy, CBT-I, relaxation exercise, use of lactuca seeds and sleep hygiene. Ten were non-randomized trials testing the efficacy of acupuncture [49]; mindful yoga [50]; music listening relaxation [51] and general relaxation [52,53]; cognitive behavioral therapy interventions [54,55]; mindfulness [56]; massage therapy [57] and tai-chi [58]. The sample size of all included studies ranged from a minimum of 13 to a maximum of 215 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the included studies, six were RCT [43][44][45][46][47][48], testing the efficacy of the following different interventions: use of lavender cream, pharmacotherapy, CBT-I, relaxation exercise, use of lactuca seeds and sleep hygiene. Ten were non-randomized trials testing the efficacy of acupuncture [49]; mindful yoga [50]; music listening relaxation [51] and general relaxation [52,53]; cognitive behavioral therapy interventions [54,55]; mindfulness [56]; massage therapy [57] and tai-chi [58]. The sample size of all included studies ranged from a minimum of 13 to a maximum of 215 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the included studies, six included healthy women with no complaints [46,50,52,53,55,57], seven included healthy women with self-reported sleep problems [43, 44, 47-49, 51, 54]; one study had participants with insomnia diagnosis [45], one reported data for obese women [56] and one included women with clinical depression [58]. Furthermore, the majority of the included studies (n=10) used only self-reported measures as outcomes; two studies [44,53] used only actigraphy and four studies [45,50,54,55] used both subjective/objective sleep parameters (diaries or actigraphy) and self-reported measures. Only four of the included studies carried out follow ups [43,44,48,53].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a non-randomized controlled pilot study, Lee & Gay implemented a sleep improvement protocol for antepartum patients, which consisted of sleep hygiene strategies and cognitive behavioral therapies for dealing with stress and worry. (12) They report that such an intervention is both feasible and efficacious; while sleep duration was not different between the experimental and control group, overall sleep disturbances were significantly less after the implementation of the protocol. Our findings reinforce the need for such studies and provide additional support for unit modifications and environmental changes, such as timing of lab draws and physician rounding, to improve sleep hygiene specifically.…”
Section: Discussionmentioning
confidence: 97%
“…(8–10) Only two studies to date have examined patterns of sleep disturbances among hospitalized antepartum patients. (11, 12) Therefore, the purpose of our study was to examine sleep quality among hospitalized antepartum patients.…”
Section: Introductionmentioning
confidence: 99%